Recent advances of pathomics in colorectal cancer diagnosis and prognosis - Wu, Yihan; Li, Yi; Xiong, Xiaomin; Liu, Xiaohua; Lin, Bo; Xu, Bo (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is one of the most common malignancies, with the third highest incidence and the second highest mortality in the world. To improve the therapeutic outcome, the risk stratification and prognosis predictions would help guide clinical treatment decisions. Achieving these goals have been facilitated by the fast development of artificial intelligence(AI) -based algorithms using radiological and pathological data, in combination with genomic information. Among them, features extracted from pathological images, termed pathomics, are able to reflect sub-visual characteristics linking to better stratification and prediction of therapeutic responses. In this paper, we review recent advances in pathological image-based algorithms in CRC, focusing on diagnosis of benign and malignant lesions, microsatellite instability, as well as prediction of neoadjuvant chemoradiotherapy and the prognosis of CRC patients.